Buku-buku Terbaru dalam Kajian Disabilitas - Inklusi, Jurnal (INKLUSI, 2019)
Dalam review kali ini, editor Jurnal INKLUSI memilih lima buku terbaru dalam kajian disabilitas untuk diperkenalkan kepada sidang pembaca sekalian. Lima buku dimaksud adalah:  The Palgrave Handbook of Disability and Citizenship in the Global SouthAuthor(s): Brian Watermeyer, Judith McKenzie, Leslie SwartzPublisher: Springer International Publishing;Palgrave Macmillan, Year: 2019ISBN: 978-3-319-74674-6;978-3-319-74675-3Prevention of Chronic Diseases and Age-Related DisabilityAuthor(s): Jean-Pierre MichelSeries: Practical Issues in GeriatricsPublisher: Springer International Publishing, Year: 2019ISBN: 978-3-319-96528-4,978-3-319-96529-1Accessible America: A History of Disability and DesignAuthor(s): Bess WilliamsonPublisher: New York University Press, Year: 2019ISBN: 1479894095,9781479894093The Science and Politics of Work Disability PreventionAuthor(s): Ellen MacEachen (ed.)Publisher: Routledge, Year: 2019ISBN: 9781138335318, 9781138335301The Routledge Handbook of Disability Arts, Culture, and MediaAuthor(s): Bree Hadley, Donna McDonaldSeries: Routledge International HandbooksPublisher: Routledge, Year: 2019ISBN: 9780815368410, 9781351254687Deskripsi lengkap silakan unduh versi PDF.